Interleukin-4 and Interleukin-13 Gene Polymorphisms in Children With Idiopathic Nephrotic Syndrome - Al Rushood, Maysoun; Al-Eisa, Amal A.; Haider, Mohammad Z. (Frontiers in Pediatrics, 2020)
Background: Idiopathic Nephrotic syndrome (INS) is an immune-mediated disease in which a number of cytokines, including IL-4 and IL-13, have been implicated in the pathogenesis. Cytokine gene polymorphisms might affect their levels and activity. Therefore, may affect INS susceptibility and response to treatment. The aim of the study was to determine the association of IL-4 and IL-13 gene polymorphisms and INS susceptibility and their effects on steroid responsiveness in children. Methods: The polymorphisms in IL-4 and IL-13 genes were detected by PCR-RFLP in 155 INS patients and 64 controls. Results: A total of 132 steroid-sensitive (SS) and 23 steroid resistance (SR) INS patients; mean age 7.3 ± 4.0 years, were included. Male: Female ratio was 2:1. No significant statistical differences were detected in the frequency of CC, CT, and TT genotypes of IL-4 gene compared to controls (P = 0.57, 0.61, and 1.00, respectively). There was no significant difference in the T and C-allele frequencies, in SS and SR subgroups. Analysis of IL-13 gene polymorphism also did not show significant statistical differences in the frequency of QQ, RQ, and RR genotypes compared to controls (P = 0.74, 1.00, and 0.68, respectively). No significant difference was found in the Q and R-allele frequency. However, the heterozygous RQ genotype of the IL13 gene was significantly higher in SS INS patients compared to the SR INS cases (P = 0.04). Conclusion: Our findings did not show an association between IL-4 and IL-13 gene polymorphisms and INS susceptibility. However, IL-13 RQ genotype was expressed more in children with INS who are steroid sensitive.